2003
DOI: 10.1021/jo020593r
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Aryllithiums Tethered to Methylenecycloalkanes:  Stereoselective Synthesis of 4a-Substituted cis-Hexahydrofluorenes

Abstract: The cyclization of an aryllithium tethered to a methylenecycloalkane, generated from 2-(o-bromobenzyl)-1-methylenecycloalkanes 1, 2, and 3 by low-temperature lithium-bromine exchange, has been found to be a kinetically slow but thermodynamically favorable process that proceeds at a convenient rate in an exclusively 5-exo fashion when solutions of the aryllithium in n-heptane-di-n-butyl ether (9:1 v/v) are warmed to 45 degrees C. The cyclization affords stereoisomerically pure cis-fused products (7 and 8) when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The stereoselective preparation of a range of 4a-substituted cis-hexahydrofluorenes has been demonstrated by treatment of 98b with alternative electrophiles. 46 The regiospecific intramolecular carbolithiation of 2-lithio-N,Ndiallylanilines was reported simultaneously by Liebeskind and Bailey as a route to 3-substituted indolines. 47 Following these reports several enantioselective variants of this methodology were developed (Table 3).…”
Section: Intramolecular Carbolithiationsmentioning
confidence: 93%
See 1 more Smart Citation
“…The stereoselective preparation of a range of 4a-substituted cis-hexahydrofluorenes has been demonstrated by treatment of 98b with alternative electrophiles. 46 The regiospecific intramolecular carbolithiation of 2-lithio-N,Ndiallylanilines was reported simultaneously by Liebeskind and Bailey as a route to 3-substituted indolines. 47 Following these reports several enantioselective variants of this methodology were developed (Table 3).…”
Section: Intramolecular Carbolithiationsmentioning
confidence: 93%
“…45 Cyclisation of aryllithium tethered methylenecycloalkanes 97a-c (formed by bromine-lithium exchange of 96a-c) facilitated the synthesis of carbotricyclic structures 99a-c (Scheme 26). 46 The rigid transition state geometry for ring closure with resulting conformational constraints of the substituents enabled formation of stereoisomerically pure cisfused products when the methylenecycloalkane is five-or sixmembered (99a,b). However, due to the greater flexibility, cyclisation of the larger seven-membered substrate 99c is less stereoselective and a 1 : 2 mixture of cis : trans isomers was isolated after protonation with methanol.…”
Section: Intramolecular Carbolithiationsmentioning
confidence: 99%
“…In all cases, the addition of tBuLi to the unsubstituted alkene in 2a was competitive with the cyclization reaction (see Supporting Information). It has been shown that the rate of carbolithiation can be increased by performing the reactions at higher temperatures, [27] so the reaction mixtures were warmed to 50°C with toluene as the solvent to avoid a protonation of the aryllithium intermediate (see Table 2, Entry 6). It has been shown that the rate of carbolithiation can be increased by performing the reactions at higher temperatures, [27] so the reaction mixtures were warmed to 50°C with toluene as the solvent to avoid a protonation of the aryllithium intermediate (see Table 2, Entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of a phenyl group to the alkene to stabilize the organolithium compound generated by the carbolithiation [26] also did not favor the intramolecular reaction, and deiodinated N-benzylpyrrole 4b was the only product (see Table 2, Entries 4 and 5). It has been shown that the rate of carbolithiation can be increased by performing the reactions at higher temperatures, [27] so the reaction mixtures were warmed to 50°C with toluene as the solvent to avoid a protonation of the aryllithium intermediate (see Table 2, Entry 6). However, similar results were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…General spectroscopic and chromatographic procedures, methods used for the purification of reagents and solvents, and precautions regarding the manipulation of organolithiums have been previously described. 1,5,12 The concentration of commercial solutions of t-BuLi in pentane was determined immediately prior to use by the method of Watson and Eastham. 13 The preparations of 3-[(t-butyldimethyl)siloxy]-6-iodo-1-hexene (6), trans-2-methyl-1-(t-butyldimethylsiloxy)cyclopentane (7), cis-2-methyl-1-(t-butyldimethylsiloxy)cyclopentane (8), and cis-2-[(t-butyldimethylsilyl)methyl]cyclopentanol (9) have been previously described.…”
Section: Methodsmentioning
confidence: 99%